Beetle Swarm Optimization Algorithm-Based Load Control with Electricity Storage. (25th November 2020) - He, Hengjing; Zhou, Shangli; Zhang, Leping; Lin, Junhong; Chen, Weile; Wu, Di
Abstract : Based on the intelligent bidirectional interactive technology, this paper studies the flexible working mode and optimal power consumption strategy of several typical power consumption loads including energy storage equipment. Based on the real-time price scheme, the objective function and constraints are obtained, and the adaptive algorithm for beetle swarm optimization with variable whisker length is used to optimize so that the electric equipment can automatically change its power load through the intelligent terminal and even work in the way of reverse power transmission. The proposed optimal scheduling algorithm can not only maximize the interests of users but also ensure the minimum peak to average ratio so as to realize peak shaving and valley filling. Simulation results verify the effectiveness of the algorithm.